"Dread to treat" patients in cardiac surgery: Global strategies for interacting with cardiothoracic patients with substance use disorders. Issue 12 (14th October 2019) - Allespach, Heidi; Stahl, Kenneth D.
Abstract: Patients with substance use disorders (SUDs) who undergo valve repair or replacement are often readmitted to the hospital after discharge secondary to recidivism. These "dread to treat" patients pose a unique dilemma for cardiac surgeons who often must make the extremely difficult decision of whether to perform a valve replacement in a recidivist patient with SUDs. This editorial focuses on illuminating strategies which surgeons can administer to patients with SUDs to improve quality of care and reduce provider distress.